Case-based audit and feedback around a decision aid improved antibiotic choice and duration for uncomplicated cystitis in primary care clinics. Issue 3 (9th July 2021) - Grigoryan, Larissa; Zoorob, Roger; Germanos, George; Sidani, Mohamad; Horsfield, Matthew; Khan, Fareed; Zare, Mohammad; Goebel, Melanie; Atmar, Robert; Trautner, Barbara
Abstract : Objectives: The objective of our study was to evaluate the impact of a multifaceted stewardship intervention on adherence to the evidence-based practice guidelines on treatment of uncomplicated cystitis in primary care. We hypothesised that our intervention would increase guideline adherence in terms of antibiotic choice and duration of treatment. Design: A preintervention and postintervention comparison with a contemporaneous control group was performed. During the first two study periods, we obtained baseline data and performed interviews exploring provider prescribing decisions for cystitis at both clinics. During the third period in the intervention clinic only, the intervention included a didactic lecture, a decision algorithm and audit and feedback. We used a difference-in-differences analysis to determine the effects of our intervention on the outcome and guideline adherence to antibiotic choice and duration. Setting: Two family medicine clinics (one intervention and one control) were included. Participants: All female patients with uncomplicated cystitis attending the study clinics between 2016 and 2019. Results: Our sample included 932 visits representing 812 unique patients with uncomplicated cystitis. The proportion of guideline-adherent antibiotic regimens increased during the intervention period (from 33.2% (95% CI 26.9 to 39.9) to 66.9% (95% CI 58.4 to 74.6) in the intervention site and from 5.3% (95% CI 2.3 to 10.1) to 17.0% (95% CI 9.9 to 26.6) in the control site). The increase in guideline adherence was greater in the intervention site compared with the control site with a difference-in-differences of 22 percentage points, p=0.001. Conclusion: A multifaceted intervention increased guideline adherence for antibiotic choice and duration in greater magnitude than similar trends at the control site. Future research is needed to facilitate scale-up and sustainability of case-based audit and feedback interventions in primary care.